Reaching & teaching them all : making quick and lasting connections with every student in your classroom - Yuill, Amanda (Markham, Ontario : Pembroke Publishers, 2018)
"This remarkable book shows you how to connect with students, get to know what makes them tick, and what makes them behave and learn the way they do (or don't!). The conversational styles is supported by well-researched information on students with challenges, and those students who challenge a teacher. This practical book shows you how to use body language, humor, shared experiences, and curriculum to engage students, manage the classroom, and support learning. A comprehensive approach to improving the learning environment in your classroom, the book is full of fresh strategies for connecting with students and offers valuable insights into applying these strategies in classrooms, both with groups and one-on-one."--
Includes bibliographical references (pages 111-114).
Keywords: Teacher-student relationships; Effective teaching